BER Performance of OFDM System with various OFDM frames in AWGN, Rayleigh and Rician Fading Channel - Benarji, B; Sasibhusana Rao, G; Pallam Setty, S (International Journal of Computer Sciences and Engineering, 2015)
Wireless technology has become the most exciting area during the past decades and also brings with it a whole host of complex design issues, concerning network design, signal detection, interference cancellation, and resource allocation. In the field of communication systems Orthogonal Frequency Division Multiplexing (OFDM) is being widely used for bulk data in single frequency band i.e., encoding digital data on multiple carrier frequency and for its ability to enhance the data rate and reduce the bandwidth. In this paper, the comparison of the performance of OFDM system using Quadrature Amplitude Modulation (QAM) under the influence of AWGN, Rayleigh, and Rician fading channels are analysed. Simulation of OFDM signals are carried out with different faded signals by increasing the number of OFDM frames in AWGN, Rayleigh and Rician fading channels to understand the effect of channel fading and to obtain optimum value of Bit Error Rate (BER) for different number of antennas.